Development and charecterization of an itraconazole solid -lipid dispersion formulation using spray drying technique for improved oral bioavailability - Ganesh. M; Chandra shekar. B; Madhusudan rao. Y (International Journal of Pharmacy and Analytical Research, 2015)
Objective- The purpose of this research to prove the efficacy of the lipid excipients in improving the aqueous dissolution and in vivo permeation of poorly soluble drugs by designing the solid dispersions. Methods- Itraconazole classified as a BCS class II compound .Itraconazole is one of the triazole antifungal agents that inhibits cytochrome P-450-dependent enzymes resulting in impairment of ergosterol synthesis., ITZ has a strongly pH dependent solubility (pKa 3.7) with reported solubilities in acidic and neutral media of approximately 4 μg/mL and 1 ng/mL respectively. While limited by poor aqueous solubility, the highly lipophilic nature of the compound (Clog P) 6.26 allows for high permeability of intestinal membranes. Due to its poor solubility it is a challenging task to prepare a formulation for oral route of administration. Spray drying approach is applied to prepare the drug loaded solid dispersions into free flowing solid particles. Results- Itraconazole incorporated solid-lipid particles it is assumed to have a higher aqueous dissolution of drug due to morphological conversion of the drug and reduced particle size. From the results it has been identified that the one composition (ISDL3) has shown optimum results. The solubility has enhanced by 4 -5 times, dissolution by 3 – 4 times, the ISDL3 (the ITR : Lipid mixture ratio was maintained at 1 : 1 ratio), with high drug content of 94% has been found as best formulation, giving lipid-solid dispersion an edge over plain drug and solid dispersions.